Clinical usefulness of the S-O clip during colorectal endoscopic submucosal dissection in difficult-to-access submucosal layer - Okamoto, Yuki; Oka, Shiro; Tanaka, Shinji; Inagaki, Katsuaki; Tanaka, Hidenori; Matsumoto, Kenta; Boda, Kazuki; Yamashita, Ken; Sumimoto, Kyoku; Ninomiya, Yuki; Chayama, Kazuaki (Endoscopy International Open, 2020)
Background and study aims In colorectal endoscopic submucosal dissection (ESD), the S-O clip improves the accessibility to the submucosal layer of the colon. However, its safety and usefulness in difficult colorectal ESDs are unclear. Thus, in this study, we aimed to assess the effectiveness of the S-O clip in colorectal ESD in the difficult-to-access submucosal layer. Patients and methods From January 2016 to December 2016, 189 consecutive cases of colorectal ESD were performed at Hiroshima University Hospital before the S-O clip was introduced. Between January 2017 and June 2018, among 271 consecutive colorectal ESD cases, 41 cases were performed colorectal ESD using the S-O clip. We compared outcomes between the two groups (41 cases with S-O clip [use group] and 189 cases without S-O clip [non-use group]) using propensity score matching. Results Prior to propensity score matching, 41 cases with the S-O clip (use group) and 189 cases without the S-O clip (non-use group) were extracted. The degree of submucosal fibrosis was more severe and the procedure time was longer in the use group than in the non-use group. In the use and non-use groups, en bloc resection (100 % vs. 94.7 %) and complete en bloc resection (100 % vs. 92.6 %) rates were satisfactory. After propensity score matching, 33 cases in each group were extracted. As a result, complete en bloc resection rate was significantly higher in the use group than in the non-use group (100 % vs. 84.9 %).Conclusion The S-O clip is effective and can be used safely in colorectal ESD in the difficult-to-access submucosal layer.